Patient Reported Outcomes of Pastoral Care in a Hospital Setting. Issue 4 (2nd October 2019) - Lobb, Elizabeth A.; Schmidt, Susanne; Jerzmanowska, Natalia; Swing, Ashley M.; Thristiawati, Safrina
Abstract : This study aimed to establish whether Pastoral Care (PC) visits were an effective component of a hospitalized patient's overall health experience. Outcomes of PC visits were reported by 369 patients in 7 sites across Australia. The patient reported outcomes of PC visits included: the patients felt they could be honest with themselves, with a sense of peace, a better perspective of their illness, less anxiety, and felt more in control. Five factors of the PC visit significantly related to higher patient's overall outcomes: (a) having more Pastoral Care visits ( p  < 0.5 0 R 0.778, CI 0.17–1.38); (b) the patient was able to talk about what was on their mind ( p  < 0.01, OR1.48, CI 0.58–2.37); (c) they had something to be hopeful about ( p  < 0.01 OR1.18, CI 0.51–1.85); 4); the visit focused on decisions about the patient's health care ( p  < 0.05, OR0.70, CI 0.05–1.35); and (d) a belief in God/Higher Being ( p  < 0.01, OR 1.01, CI 0.43–1.71).